Cardiovascular complications of diabetes: recent insights in pathophysiology and therapeutics. Issue 5 (September 2011) - Marette, André; Sweeney, Gary
Cardiovascular complications represent the principal cause of death in patients with Type 2 diabetes. It is therefore of great importance to dissect the genetic determinants and molecular mechanisms responsible for diabetic cardiovascular complications. New research is of particular importance since, somewhat unexpectedly, large-scale clinical trials have indicated that glycemic control does not appear to have the anticipated major influence as a factor dictating cardiovascular outcome in diabetics. Hence, additional pathophysiological factors such as dyslipidemia, as well as proinflammatory and proatherosclerotic mechanisms, need to be more carefully examined. In this article, we will focus on recent studies in both animal models and humans as well as cellular mechanistic studies that advance our knowledge on the role of dyslipidemia, inflammation and atherosclerotic events in the cardiovascular complications of diabetes. We also translate our focus on research insights to related therapeutic opportunities.